Changes in the pattern of polycyclic aromatic hydrocarbons in soil treated with biochar from a multiyear field experiment. (March 2019) - Rombolà, Alessandro G.; Fabbri, Daniele; Baronti, Silvia; Vaccari, Francesco Primo; Genesio, Lorenzo; Miglietta, Franco
Abstract: The influence of biochar added to an agricultural soil on polycyclic aromatic hydrocarbon (PAH) levels, PAH diagnostic ratios and soil properties was investigated in a five-year field experiment. The experiment was carried out in an Italian vineyard and included two biochar treatments: 16.5 t ha −1 of biochar applied in 2009 (soil B); 16.5 t ha −1 in 2009 and further 16.5 t ha −1 in 2010 (soil BB). A set of 75 samples that included five replicates and a control soil (untreated) was characterized in terms of organic carbon, pH, cation exchange capacity (CEC), bulk density and concentration of PAHs. Biochar addition to soil caused an increase in organic carbon, pH and CEC, and a decrease of bulk density. After almost two years the first application of biochar, PAH concentrations were higher in soil B (56 ng g −1 ) and BB (153 ng g −1 ) in comparison to control soil (24 ng g −1 ). Thereafter, PAH concentrations decreased significantly, but the original PAHs levels were reached only in soil B after five years. The naphthalene/(naphthalene + phenanthrene) ratios were higher in the treated soils in accordance to the dominance of naphthalene in the original biochar. The cross plots naphthalene/(naphthalene + phenanthrene) vs. fluoranthene/(fluoranthene + pyrene) enabled to trace the signature of biochar PAHs up to five years after its first application. Diagnostic ratios can be a useful tool to study the persistence of PAHs introduced in soil by biochar when the pattern of these contaminants in biochar and original soil are different. Highlights: The addition of quality biochar resulted in a significant increase of PAHs in soil. Contamination decreased with time and was highest after a dry period. Original PAH levels were not restored after four years from two amendments. Biochar addition to soil increased pH, CEC and decreased bulk density. Naphthalene phenanthrene ratios confirmed the imprinting of biochar derived PAHs.